Non-equilibrium induction of tin in germanium: towards direct bandgap Ge1−xSnx nanowires - Subhajit Biswas (Nature Portfolio, 2016)
Direct band gap nanostructures compatible with Si-based electronics are actively investigated. Here, Biswas et al. incorporate unusually large amounts of tin in germanium nanowires by non-equilibrium kinetic trapping, and optical characterizations suggest that the nanowires exhibit a direct band gap.